2016
DOI: 10.1177/1941874415611180
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime-Associated SIRPIDs in a Patient With Normal Renal Function

Abstract: Cefepime has been associated with encephalopathy and with nonconvulsive seizure activity, primarily in patients with renal impairment. Here, we report a case of cefepime-associated encephalopathy in a patient with normal renal function with stimulus-induced rhythmic activity seen on electroencephalogram, which resolved on discontinuation of cefepime. We bring this to the attention of the neurohospitalist community, as cefepime is widely used in the hospital setting, and cefepime-related neurotoxicity may go ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Johnson et al 15 reported a case having normal renal function with CIE showing stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs). However, our patients with CIE did not show SIRPIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al 15 reported a case having normal renal function with CIE showing stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs). However, our patients with CIE did not show SIRPIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports have found that the EEG patterns in patients with CIE included rhythmic triphasic waves that were nonreactive to stimulation, 5,6,12,13 nonconvulsive status epilepticus with generalized spikes, and slow-wave or sharp and slow-wave activity. 6,14 Johnson et al 15 reported a case having normal renal function with CIE showing stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs). However, our patients with CIE did not show SIRPIDs.…”
Section: Jcnmentioning
confidence: 99%
“…5 This is an interesting phenomenon associated with cefepime neurotoxicity, which has only been reported in case reports thus far. 53,54 Although stimulus-induced rhythmic and/or periodic discharges were initially considered to be associated with a heightened seizure risk, recent work has shown that the stimulus-induced characteristic does not confer a higher seizure risk beyond that of the electrographic pattern and may even arise from the encephalopathy. [55][56][57][58][59] Our case series emphasizes TWs as a hallmark of cefepime-induced encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…2 ) und periodischen lateralisierten Entladungen. Zudem kommt es teils zu epileptischen Anfällen, bei insgesamt eingeschränkter Datenlage sind bis zu 11% epileptische Anfälle unter Therapie beschrieben 38 40 . In der eigenen Erfahrung der Autoren ist das Auftreten von epileptischen Anfällen im täglichen Alltag unter antibiotischer Therapie doch eine Seltenheit und allenfalls unter der Behandlung Penemen zu beachten, in der Literatur ist diesbezüglich insbesondere eine Häufung unter Imipenem beschrieben Zudem sind die meisten Arbeiten, die sich mit Anfälle im Rahmen einer antiinfektiven Therapie befassen, rein beschreibend, so dass ein eindeutiger Zusammenhang mit der Medikation nicht zu sichern war, wenngleich die doch unterschiedlichen beschriebenen Raten von Anfälle unter einer solchen Therapie zwischen verschiedenen Präparaten zumindest einen teilweisen Zusammenhang nahelegt.…”
Section: Medikamente Mit Einfluss Auf Das Eegunclassified